PENGARUH SENAM A-PIK (ANTI PIKUN) TERHADAP PENURUNAN DEMENSIA PADA LANSIA - awalia dinis rawildati, - (2020)
In the elderly there will be an aging process in the brain which is a process of degeneration, causing neuropsychological disorders, one of the common health problems is dementia. Dementia is a disease that occurs when a person has started the aging process due to the effects of decreased cognitive function. One way to prevent or slow down dementia is through physical activity. However, there are still very many who are lazy to do physical activity. So that every year cases of dementia are always increasing. The consequences that will occur if changes in the elderly are not quickly handled properly will have a bad impact on the health of the elderly as a whole. Therefore, the aim of this study is to assess whether with physical activity especially with A-Pik Exercise. can slow the rate of dementia in the elderly. In this study, using a pre-experimental form of research. The method used in this research is One grop pretest-post test design, with the population in this study is 78 with a sample of 22 elderly aged 50-70 years who live in Cibenying Kidul district. The results of this study obtained p (0,000) <0.05 which indicates that there is a significant difference after the elderly are given Senam A-Pik treatment.